Association of Maternal Serum C- Reactive Protein Levels with Severity of Preeclampsia - Fatemeh Mirzaie; Fatemeh Rahimi-Shorbaf; Amir Hossian Kazeronie (Acta Medica Iranica, 2009)
The aim of this study was to investigate C-reactive protein (CRP) level in preeclampsia (PE) and its association with the severity of the disease. This cross-sectional study included 43 women with mild PE, 43 women with severe PE, and 43 healthy pregnant. They were selected in the third trimester of pregnancy in the Afzalipour Hospital, Kerman, Iran, from March 2006 to March 2007. Mean diastolic pressure and level of proteinuria were used as indicators of the severity of the disease. The results were analyzed by t-test and spearman's rank correlation coefficient. Hemoglobin, aspartate and alanine transaminase, creatinine and urine protein excretion, serum CRP, and alkaline phosphatase were higher in women with PE. There were significant correlations between serum CRP levels and diastolic blood pressure (r = 0.5, P = 0), urinary protein excretion (r = 0.5, P = 0), creatinine (r = 0.2, P = 0.003), spartate transaminase (r = 0.3, P = 0), alanine transaminase (r = 0.2, P = 0.006), and Hemoglobin (r = 0.2, P = 0.001). There were a negative correlation between serum CRP and weight of the new born (r = -0.09, P = 0.01) and gestational age in the time of delivery (r = -0.07, P = 0). We showed higher levels of CRP in women with PE. Elevated serum levels of CRP in PE women are, thus, correlated with severity of disease.